Digital Marketing As a Means of Developing Small And Medium Enterprises Businesses In The Klaten City - Putri Kusumawati; Agus Suyatno; Safitri Nur; Lyly Katniaty (LPPM Universitas Duta Bangsa Surakarta, 2021)
In the era of globalization, the world of marketing will continue to develop with the times. The strategy that is implemented of course also continues to evolve following the rapid advancement of the digital world. Small and medium enterprises in the Klaten area have started to market their brands and products through digital marketing. And it is hoped that using this marketing method can improve the economy of small and medium enterprises in the Klaten city. Digital Marketing Research as a means of developing small and medium enterprises in the Klaten city uses two data, namely primary data and secondary data. Primary data was obtained by conducting interviews using a questionnaire with 119 respondents. The selection of respondents was based on the consideration that the respondent was a small and medium business actor in the Klaten area. Secondary data is data obtained from existing and relevant data sources such as journals, books and writings that support this research. The advantage of this digital marketing method is that it is accessible for all groups and also all regions. Judging from 119 responses, 60.5 percent were male, 39.5 percent female. Of the 119 respondents, 64.7 percent strongly agree that digital marketing is a new breakthrough to help micro, small and medium enterprises. 62.2 percent agree that digital marketing is one of the micro, small and medium enterprises. 60.5 percent strongly agree that digital marketing is one of the solutions to improve the economy of micro, small and medium enterprises. 60.5 percent strongly agree that digital marketing is the choice of the day. And 61.3 percent is very efficient if digital marketing is sfor micro, small and medium enterprises.